104k views
5 votes
Help........ Again and thanks

Help........ Again and thanks-example-1
User Ignatov
by
6.0k points

1 Answer

3 votes

Answer:

x=3, y=1

Explanation:

2x+y =7

3x-4y =5

Multiply the first equation by 4 so we can eliminate y

4(2x+y =7)

8x +4y =28

Add this to the second equation

8x +4y =28

3x-4y =5

----------------

11x = 33

Divide by 11

11x/11=33/11

x=3

Now we still need to find y

2x+y=7

2(3)+y =7

6+y=7

Subtract 6 from each side

6-6+y=7-6

y= 1

User Warjeh
by
5.9k points